The significance of green innovation efficiency of green low-carbon circular economy for sustainable cities in western China—Empirical evidence from Chongqing municipality - Panfeng Li (Frontiers in Public Health, 2025)
IntroductionThe Green Low-Carbon Circular Economy (GLCCE) represents a critical pathway toward achieving sustainable development, particularly within the context of ongoing urbanization in western China. This study investigates the role of open innovation, specifically through green innovation efficiency (GIE), in advancing GLCCE and fostering sustainable urban development. Chongqing Municipality serves as an empirical case, utilizing data from 2014 to 2023.MethodsAn evaluation indicator system for GLCCE was established, encompassing dimensions of economic and social development, green development, low-carbon development, and circular development. The entropy weight-Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) model was employed to calculate Chongqing's GLCCE composite index. Subsequently, a panel regression model was developed to assess the impact of green innovation efficiency (GIE) on environmental quality. In this model, SO2 concentration was the dependent variable, GIE was the core explanatory variable, and control variables included openness to external trade (EXT), information technology level (ITL), urban cultural level (CUL), and research and development investment (RDI).ResultsThe entropy weight-TOPSIS model revealed that Chongqing's GLCCE composite index increased from 0.405 in 2014 to 0.684 in 2023, with a peak of 0.866 in 2020, indicating significant overall progress in GLCCE implementation. The panel regression analysis demonstrated that GIE significantly reduces SO2 concentration, with a coefficient of −0.218 (p < 0.05). This signifies that a 1% increase in GIE is associated with a 0.218-unit decrease in SO2 concentration, underscoring GIE's role in improving environmental quality through technological advancement and resource optimization.DiscussionThe findings highlight substantial advancements in Chongqing's GLCCE and underscore the pivotal contribution of green innovation efficiency to this progress, particularly in enhancing environmental quality. The significant negative relationship between GIE and SO2 concentration suggests that fostering innovation is crucial for urban sustainability and improving living standards. This study provides empirical evidence and offers valuable policy insights for other cities in western China aiming to promote sustainable development through the GLCCE framework and strategic open innovation initiatives.